(untitled) (Journal of Philosophy Culture and Political Science, 2020)
Based on the questionnaire, in-depth interview method and focus group discussions, the article reveals the social and professional intentions of students from Kazakhstan after graduating from foreign universities, the reasons for the irrevocable migration to Kazakhstan. During the survey, the authors asked themselves to try to answer the following questions: What affects the decision of youth to study in foreign universities? What are the plans for students from Kazakhstan after graduating from foreign universities? What are the criteria for youth to return to Kazakhstan? What is the reason for the unwillingness of young people studying abroad to return to Kazakhstan? The studies revealed external globalization and internal country-specific factors affecting the “irrevocable” migration of Kazakhstani youth studying outside the country. The authors come to the conclusion that important measures of the prestige of students to study in Kazakhstan are all measures to expand the academic and managerial independence of higher educational institutions, improving the quality of domestic education, modernizing educational programs that are oriented to the labor market and contribute to the preparation of a competitive specialist by domestic universities. Key words: educational migration, “irrevocable migration”, “brain drain”, globalization, sense of homeland.